2008
DOI: 10.1007/s00464-008-0049-z
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Hartmann’s procedure through the stomal side: a new even more minimal invasive technique

Abstract: Background Several minimal invasive, mainly laparoscopic-assisted, techniques for reversal of Hartmann's procedure (HP) have been published. The purpose of this pilot study was to assess a minimal invasive procedure through the stomal site that may compare favorably with open or laparoscopic-assisted procedures in terms of operative time, hospital stay and postoperative complications. Methods HP reversal through the stomal side was attempted in 13 consecutive patients. Lysis of intraabdominal adhesions was don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…A similar technique like SIR, but laparoscopically-assisted, has been published before [11,16]. In contrast with other laparoscopic HP reversal procedures, SIR was found to have a shorter operation time compared to HP reversal by laparotomy.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…A similar technique like SIR, but laparoscopically-assisted, has been published before [11,16]. In contrast with other laparoscopic HP reversal procedures, SIR was found to have a shorter operation time compared to HP reversal by laparotomy.…”
Section: Discussionmentioning
confidence: 97%
“…The only exclusion criterion for SIR was an accompanying symptomatic abdominal wall hernia that needed (open) correction. A brief description of the surgical procedure of SIR is stated below [11]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, utilization of the colostomy site for laparoscopic reversal of Hartmann' s procedure was introduced, and several studies have shown the feasibility of the procedure. [1][2][3][4][5] It allows for the colostomy site as an access port for the operation. However, single port surgery is technically more challenging than multiport surgery due to instrument interference and inaccessible angles from a single site.…”
Section: Introductionmentioning
confidence: 99%